2014
DOI: 10.1002/cctc.201300974
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Fluidized Catalytic Cracking Catalyst on Ensemble and Individual Particle Level by X‐ray Micro‐ and Nanotomography, Micro‐X‐ray Fluorescence, and Micro‐X‐ray Diffraction

Abstract: A combination of advanced characterization techniques: synchrotron X‐ray micro‐ and nanotomography, micro‐X‐ray fluorescence, and micro‐XRD have been used to characterize a commercial spent equilibrium fluid catalytic cracking catalyst (ECAT) at both the ensemble and individual particle level. At the ensemble level, X‐ray microtomography was used to determine the average size, shape, and respective distributions of over 1200 individual catalyst particles. This information is important to determine performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…1, the morphological information obtained by nano-TXM is displayed. The particle appears to be a typical FCC catalyst particle when compared with previous studies181920212941: it has a diameter of about 40 μm, shows a denser surface layer of 1–2 μm thickness and a complex macro-pore structure throughout the rest of the particle; the total porosity was determined to 18.8%. In this study, we additionally performed a pore throat analysis45, which revealed a pore throat size distribution peak at about 320 nm.…”
Section: Resultsmentioning
confidence: 58%
“…1, the morphological information obtained by nano-TXM is displayed. The particle appears to be a typical FCC catalyst particle when compared with previous studies181920212941: it has a diameter of about 40 μm, shows a denser surface layer of 1–2 μm thickness and a complex macro-pore structure throughout the rest of the particle; the total porosity was determined to 18.8%. In this study, we additionally performed a pore throat analysis45, which revealed a pore throat size distribution peak at about 320 nm.…”
Section: Resultsmentioning
confidence: 58%
“…Furthermore, no information about size and shape of the mesopores can be obtained because the resolution is limited. [171][172][173] Recently, Mitchell et al used synchrotron radiation X-ray tomography microscopy (SRXTM) to visualize the internal pore architecture of an industrial granule consisting of hierarchical alkaline-treated ZSM-5 zeolite and the binder attapulgite. Besides imaging porosity, the recently developed optical method based on microimaging by interference and infrared microscopy was successfully used to monitor diffusion of non-fluorescent guest molecules, such as methanol and ethanol, through nanoporous zeolites.…”
Section: Confocal Fluorescence Microscopymentioning
confidence: 99%
“…SEM image of a spent fluid cracking catalyst particle, showing a spherical particle morphology and absence of micron‐scale pores, as well as bright regions which are likely to correspond to high local concentrations of heavy metals. From Bare et al , copyright John Wiley & Sons.…”
Section: Wastes From Other Industriesmentioning
confidence: 99%